Assessment of the State of Competition in the Banking Market in the Russian Federation - Rabdanova, Anna; Bulatova, Vera (Naše gospodarstvo/Our economy, 2016)
Competition is one of the factors directly influencing the development of the banking market, the stability of the banking system, and the monetary system as a whole. This article describes the features of banking competition, methods of analysis of banking competition, and an analysis of the current state of competition in the banking market in the Russian Federation. The analysis of banking competition in the Russian Federation was performed using the concentration ratio for the top three companies and the Herfindahl-Hirschman Index. The research concludes with an assessment of the state of competition in the banking market and identification of the barriers to entering the financial services market.